Non Pharmacological Therapy in Case Study Obstacles to Physical Mobility Post Sectio Caesaria - Sri Wahyuningsih; Nurul Hayati; Hesti Adi Safitri (Nursing and Health Sciences Journal (NHSJ), 2021)
Sectio Caesarea surgery causes pain and results in changes in tissue continuity due to surgery, earlymobilization can support the patient's wound healing process because moving the limbs will preventthe stiffness of muscles and joints, reducing pain and can accelerate blood circulation to parts thathave injuries that wound healing processes become faster. This study was to explore nursing care inpostoperative Sectio Caesarea with problems with physical mobility barriers through lavenderaromatherapy in the Teratai Room RSUD dr. Hayato Lumajang. Qualitative descriptively throughcase studies. The population in this study was postoperative mothers with Sectio Caesarea in theLotus Room at RSUD Dr. Haryoto, Lumajang Regency, with a total of 10 patients in June 2020. Theuse of aromatherapy dripped onto an oxygen mask for 3 minutes, after 3 hours of analgesicadministration. Both the inhalation method with an oxygen mask and directly inhaled prove thatlavender essential oil aromatherapy can reduce the pain scale of post-section Caesarea. Thisresearch is expected with this case study report to increase knowledge and insight in applying topatients and patients families about postoperative Sectio Caesarea in the implementation of earlymobilization, as well as innovations in giving lavender aromatherapy, can also be done to post SectioCaesarea patients. And it can be used as a new experience and information to reduce pain witharomatherapy.